A Study on the Feeding Practices among Under-Five Children in Urban Slum dwellers of District Dehradun, India - Sinha, Richa; Kakkar, Rakesh; Kandpal, S D (Bangladesh Journal of Medical Science, 2016)
Background: Breast milk feeding is the first fundamental right of the child. However, there are many cultural practices associated with infant feeding of which certain undesirable practices need to be discouraged. Objectives: To assess the feeding practices of under five year children in urban slum and to determine the factors influencing it, if any. Methodology: Community based analytical cross sectional study was conducted in urban slums amongst mothers over one-year period. A house to house survey was conducted and Data was collected using a pre-tested, structured questionnaire on breastfeeding practices & data pertaining to breastfeeding practices was asked in detail from mothers of babies who were breastfed. Results: A total of 381 children were studied. A total of 87.0% of the children were delivered at health facilities and the rest at home. 65.9% received prelacteal feed in the form of water, infant milk formula, cow milk and honey. Most of the children (54.1%) received breast milk within 24 hrs of birth. 95.0% received colostrum and 67.2% received exclusive breast feeding for 6 months. It was observed that children who were exclusively breastfed for six months were found to be better nourished (51.3%). Conclusions: Majority of the mothers were practicing exclusive breast feeding, however a significant proportion of children was deprived of timely initiation of breast feeding. About 2/3 of the mothers were still practicing pre-lacteal feeds to their children. The study documents that there was significantly increased risk of PEM if the child is not exclusive breastfed for 6 months. Bangladesh Journal of Medical Science Vol.15(1) 2016 p.15-19